Connecting the Knowledge Commons - From Projects to Sustainable Infrastructure : The 22nd International Conference on Electronic Publishing - Revised Selected Papers - Leslie Chan (OpenEdition Press, 2019)
The question of sustainability in the open access movement has been widely debated, yet satisfactory answers have yet to be generated: How do we move from an approach entirely based on temporary projects to an approach based on community-based sustainable infrastructure? What kinds of social and technical infrastructures could support the Knowledge Commons? What values and services are being delivered, by which stakeholders, and for whom? What governance and financial models are possible? Given the global nature of scholarly communication, how do we ensure that the designs of the Commons are inclusive of voices from the global South? This volume collects nine selected papers presented at ELPUB2018 Conference in June 2018 in Toronto. Each paper was carefully selected, reviewed and edited to bring to an international audience the latest contributions from researchers and experts in the field. In addition to the technical issues related to interoperability of systems, research workflow, content preservation, and other services, the selected papers address the design and implementation of a community-based research communication infrastructure. ELPUB Conference has featured research results in various aspects of digital publishing for over two decades, involving a diverse international community of librarians, developers, publishers, entrepreneurs, administrators and researchers across the disciplines in the sciences and the humanities.